Точні розв’язки крайової задачі узагальненої системи Шіґесади–Кавасакі–Терамото - Музика, Лілія; Muzyka, Liliia (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті побудовано нові точні розв’язки узагальненої системи Шіґесади–Кавасакі–Терамото. На їх основі розв’язано крайові задачі з нульовими умовами Ноймана. Досліджено асимптотичну поведінку знайдених розв’язків крайових задач.; Development of methods for integrating the nonlinear differential equations and their systems is the actual problem of modern mathematical physics. The article is devoted to the non-linear evolution cross–diffusion Shigesada–Kawasaki–Teramoto system, which generalizes the classical diffusion Lotka–Voltera system. New exact solutions of the generalized Shigesada–Kawasaki–Teramoto system are built by means of exact solutions of the Fisher equation in this article. Boundary–value problem with zero Neumann conditions is investigated. Exact solutions of this problem are given. The asymptotic behaviour of these solutions is examined.
Exact Solutions of Boundary-value Problem of Generalized Shigesada–Kawasaki–Teramoto System
Keywords: система Шіґесади–Кавасакі–Терамото; система Лотки–Вольтера; точний розв’язок; узагальнене рівняння Фішера; крайова задача; нульові умови Ноймана; the Shigesada–Kawasaki–Teramoto system; the Lotka–Volterra system; exact solution; the generalized Fisher equation; boundary-value problem; zero Neumann conditions